2019
DOI: 10.1021/acs.organomet.9b00314
|View full text |Cite
|
Sign up to set email alerts
|

Late-Stage Generation of Bidentate η3-Benzophosphorine–Phosphino Ligands from a Rhodium PCcarbeneP Pincer Complex and Their Use in the Catalytic Hydrosilylation of Alkynes

Abstract: The previously reported rhodium PCcarbeneP pincer complex (1) was reacted with a range of alkynes to generate complexes 2a–e and 4a–f featuring a bidentate η3-benzophosphorine–phosphino ligand {PC3 R1,R2 (P)}. As such, a variety of electronic and steric components could be incorporated into the PC3 R1,R2 (P) ligand at a late synthetic stage. These complexes were found to be competent catalysts for the hydrosilylation of alkynes, providing high yields of (E)-alkene products. A correlation between the electrophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…In comparison to the catalysis of diphenylacetylene by Hollis et al, 22 their homobimetallic rhodium NHC complex (catalyst loading of 2−3.5 mol %) achieved 100% conversion after 2 h at 80 °C with a selectivity of 80% E and 20% Z, whereas our cyclometalated complex 2 had a conversion of 100% after only 1 h with slightly lower selectivity for the E isomer (entry 3). Young and co-workers 54 tested their PC carbene P pincer complex for the hydrosilylation of phenylacetylene among other alkynes. They conducted their reactions at room temperature with a reaction time of 24 h; however, they only achieved 35% conversion but with good E isomer selectivity (E:Z = 98:2), whereas our complex 2 had an almost quantitative conversion after 24 h at room temperature but high selectivity for the Z isomer (80%).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In comparison to the catalysis of diphenylacetylene by Hollis et al, 22 their homobimetallic rhodium NHC complex (catalyst loading of 2−3.5 mol %) achieved 100% conversion after 2 h at 80 °C with a selectivity of 80% E and 20% Z, whereas our cyclometalated complex 2 had a conversion of 100% after only 1 h with slightly lower selectivity for the E isomer (entry 3). Young and co-workers 54 tested their PC carbene P pincer complex for the hydrosilylation of phenylacetylene among other alkynes. They conducted their reactions at room temperature with a reaction time of 24 h; however, they only achieved 35% conversion but with good E isomer selectivity (E:Z = 98:2), whereas our complex 2 had an almost quantitative conversion after 24 h at room temperature but high selectivity for the Z isomer (80%).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The use of ortho substituents on the pincer diarylphosphino groups represents a steric-based strategy to impart selectivity to reactions with nonpalindromic PC carbene P complexes. We have previously found that the reaction of phenylacetylene readily occurs with 2a in a nonselective manner . Similarly, when 2d – g were reacted with phenylacetylene, mixtures of 4d – g and 4d′ – g′ were generated in approximately equal ratios, showing that little (or no) selectivity is imparted onto the pincer complex by electronic imbalance in the pincer ligand (Scheme ).…”
Section: Resultsmentioning
confidence: 96%
“…We have previously found that the reaction of phenylacetylene readily occurs with 2a in a nonselective manner. 11 Similarly, when 2d−g were reacted with phenylacetylene, mixtures of 4d−g and 4d′−g′ were generated in approximately equal ratios, showing that little (or no) selectivity is imparted onto the pincer complex by electronic imbalance in the pincer ligand (Scheme 3). However, the reaction of 2e with phenylacetylene gave rise to predominantly 4e (over 90% selectivity for 4e over 4e′ as determined via 31 P NMR spectroscopy), with phenylacetylene insertion into the Rh−P bond on the diphenylphosphino side of the pincer.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…Complex 5a was found to be a zwitterionic complex with an anionic platinum center and a cationic phosphoindolium moiety. The ligand changes from a κ 2 -P,P- to a κ 2 -C,P-chelating mode by the conversion from complex 4a to 5a …”
Section: Resultsmentioning
confidence: 99%